Simulasi Pengendali Suhu Menggunakan Algoritma Proportional, Integral, Derivative Berbasis Programmable Logic Controller Pada Modul Plant Honeywell - Kanaya, Odillia; Mulyadi, Melisa; Indriati, Kumala (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2023)
The process of heating in the food industry is often can be found, start from inserting water and the heating process begin to reach a certain temperature, so the process of controlling temperature is one of the important things in the food industry. Temperature controller is an important thing, to maintain certain temperature, so that it did not exceed or lower than needed. This system uses Honeywell programmable logic controller (PLC) as the automation based system. In this research, Honeywell PLC controller will be using proportional, integral, derivative (PID) algorithm to maintain the required temperature. The research will be using the Honeywell module in Automation Laboratorium, Engineering Faculty, Atma Jaya Catholic University of Indonesia. The heating process will begin if the water level in the tank is filled to the required level. System will turn on the heater based on the PID output in the PLC program, so the temperature is maintained to a required setpoint 35oC. The simulation system can be controlled through a human machine interface (HMI) HCix08 that was made with XDesigner Plus software. The maintained temperature has ±5% tolerance or ±1,75˚C. The result of the research shows that the best parameter for setpoint 35˚C is using a PD controller with the values for Kp is 8 and Kd is 2.